A New Sail-Backed Styracosternan (Dinosauria: Ornithopoda) from the Early Cretaceous of Morella, Spain. - José Miguel Gasulla; Fernando Escaso; Iván Narváez; Francisco Ortega; José Luis Sanz (PLoS ONE)
A new styracosternan ornithopod genus and species is here described based on a partial postcranial skeleton and an associated dentary tooth of a single specimen from the Arcillas de Morella Formation (Early Cretaceous, late Barremian) at the Morella locality, (Castellón, Spain). Morelladon beltrani gen. et sp. nov. is diagnosed by eight autapomorphic features. The set of autapomorphies includes: very elongated and vertical neural spines of the dorsal vertebrae, midline keel on ventral surface of the second to fourth sacral vertebrae restricted to the anterior half of the centrum, a posterodorsally inclined medial ridge on the postacetabular process of the ilium that meets its dorsal margin and distal end of the straight ischial shaft laterally expanded, among others. Phylogenetic analyses reveal that the new Iberian form is more closely related to its synchronic and sympatric contemporary European taxa Iguanodon bernissartensis and Mantellisaurus atherfieldensis, known from Western Europe, than to other Early Cretaceous Iberian styracosternans (Delapparentia turolensis and Proa valdearinnoensis). The recognition of Morelladon beltrani gen. et sp. nov. indicates that the Iberian Peninsula was home to a highly diverse medium to large bodied styracosternan assemblage during the Early Cretaceous.